Blue and grey urban water footprints through citizens' perception and time series analysis of Brazilian dynamics - Souza, Felipe Augusto Arguello; Bhattacharya-Mis, Namrata; Restrepo-Estrada, Camilo; Gober, Patricia; Taffarello, Denise; Tundisi, José Galizia; Mendiondo, Eduardo Mario (Hydrological sciences journal, 2021)
Predicting future water demands of societies is a major challenge because it involves a holistic understanding of possible changes within socio-hydrological systems. Although recent research has made efforts to translate social dimensions into the analysis of hydrological systems, few studies have involved citizen participation in water footprint analysis. This paper integrates time series with citizens' perceptions, knowledge and beliefs concerning sanitation elements to account for municipal blue and grey water footprints in São Carlos, Brazil, from 2009 to 2016, and potential water footprints in 2030 and 2050. In this case study, grey footprint potentially exceeds the blue water footprint by up to 35 times, and volunteered information suggested a reduction in water consumption, larger garbage production and greater investment in sanitation infrastructure from authorities. We conclude that public knowledge can be used to delineate possible water footprint scenarios and reveal paradoxes in the coevolution of socio-hydrological systems on an urban scale.